PSVIII-42 Varying the application rate of a Lactobacillus plantarum based inoculant on nutrient composition, fermentation characteristics, and digestibility of corn silage. (7th December 2018) - Acharya, I; Waugh, T; Casper, D
Abstract: The goal was to determine the optimal application rate (AR) of a Lactobacillus plantarum (LP) based silage inoculant (Nutraferma, Sioux city, IA) on nutrient composition, fermentation characteristics, and in vitro DM and NDF digestibility when ensiling whole plant corn (Channel 215–80 Brand, Monsanto Company) using a completely randomized design with 6 replicates. The treatments were: Control with no AR of LP (0-LP), or AR of 80 (80-LP), 160 (160-LP), 240 (240-LP), and 320 (320-LP) mg LP inoculant (1.3 x 10 9 cfu/g) added per kg of fresh weight. The LP inoculant was properly applied, and mixed to the corn silage followed by packing in buckets, weighing, and ensiling for 90 d. Dry matter recovery was lowest (P < 0.01) for 0-LP treated compared to remaining treatments (97.5, 99.0, 98.9, 98.6 and 98.2% for 0-LP, 80-LP, 160-LP, 240-LP, and 320-LP respectively). The DM (35.4%) and CP (8.3%) concentrations were similar ( P > 0.1) among treatments, while, ADF, NDF, ADIP, NDIP, and lignin concentrations were lower ( P < 0.01) for 80-LP comparted to the remaining treatments. The DM digestibility was greater ( P < 0.01) for LP-80 compared to LP-0, LP-160, and LP-320 with LP-240 being similar (71.9, 73.6, 72.5, 72.9, and 72.1%), while the digestibility of NDF-30h being greater ( P < 0.1) for 80-LP compared to LP-0 with remaining treatments being similar (50.2, 51.4, 50.7, 51.1, and 50.8%). The post-ensiled silage pH was higher ( P < 0.01) for 0-LP compared to the remaining treatments (4.15, 4.00, 3.93, 3.96, and 4.00). Lactic acid concentration tended to be lower (P < 0.06) for 0-LP treatment compared to the remaining treatments (4.9, 5.2, 5.3, 5.4, 5.2%). The use of LP based silage inoculant at 80 mg/kg of fresh weight has shown clear advantage over control and higher LP AR for economy and silage quality.